Agarwood prescription in Malay traditional medical manuscripts - Samsudin, Nurhusna; Hashim, Yumi Zuhanis Has-Yun; Muhammad Tormizi, Ummu Athiyah; Mohd Nasir, Asmak Muti'ah; Zainudin, Nur Umisha (2019)
Aquilaria is a species of Agarwood which is well known by many names of Gaharu in Malay, Chen xiang in China, Jin-ko in Japan and Oud in Arab countries. It is one of the most sought-after trees in the world, for its many uses and valuable properties. Aside from the widespread use in the fragrance industry, Agarwood has many applications in medicine. It is traditionally reported to be able to cure many diseases such as joint-pain, diabetics and inflammatory-related ailment and diarrhoea. Thus, this article is to discuss the applicability of Agarwood in Traditional Malay Medicine (TMM) documented in old Malay text or manuscripts. The main source of manuscripts is from the collection of the Centre of Malay Manuscript, National Library Malaysia. The scope of discussion comprises the prescriptions of TMM that include Agarwood as one of the elements of the remedies, types of diseases, process of preparing the prescription, method of treatment as well as taboos. Findings from this work is expected to be able to verify the traditional use of Agarwood towards the discovery of new evident-based alternative medicine while safeguarding TMM as national heritage.